Comparative evaluation of biochemical effects of date palm (Phoenix dactylifera) fruit extracts on paracetamol-induced hepatotoxicity in Wistar rats - O Ikponmwosa-Eweka; A.I. Eromosele (Journal of Applied Sciences and Environmental Management, 2019)
The therapeutic activity of date palm extracts (Phoenix dactylifera) against paracetamol-induced hepatotoxicity was studied in rats of the Wistar strain. Forty-eight (48) Wistar rats were assigned into 8 groups equally. Group I (normal control) were given distilled water for 14 consecutive days. Group II (negative control) received paracetamol (2 g/kg). Group III were pretreated with aqueous extract (400 mg/kg) for 7 days before receiving paracetamol (2 g/kg) for 7 additional days. Group IV were pretreated with aqueous extract (400 mg/kg) for 7 consecutive days and paracetamol (2 g/kg) for 7 additional days. Group V– received 2 g/kg of paracetamol for 7days and given 400 mg/kg aqueous extract for additional 7 days. Group VI received paracetamol (2 g/kg) for 7days followed by ethanolic extract (400 mg/kg) for 7 additional days. Group VII were co-administered paracetamol (2 g/kg) and the aqueous extract (400mg/kg) for 7 days. Group VIII were co-administered paracetamol (2 g/kg) and ethanolic extract (400 mg/kg) for 7 days. To evaluate the efficacy of the extracts on paracetamol-compromised liver in Wistar rats, the enzyme activities of ALT, AST, ALP and bilirubin concentration in serum were investigated. Treatment with aqueous and ethanolic extracts at different timing significantly (p<0.05) decreased paracetamol-induced elevation of serum concentrations of ALT, AST and bilirubin. Concurrent administration of the extracts with paracetamol conferred better hepatoprotection compared to the prophylactic and curative treatments. The present findings suggest a potential therapeutic use of Phoenix dactyliferia in treatment of liver diseases.